2021
DOI: 10.1007/s43762-021-00007-w
|View full text |Cite
|
Sign up to set email alerts
|

Administrative level, city tier, and air quality: contextual determinants of hukou conversion for migrants in China

Abstract: Hukou reform and relevant policies are being implemented in current China, but the response of migrants to hukou conversion in destinations falls short of expectation. It is significant to understand how contextual factors in destination cities affect migrants’ willingness of hukou conversion. Considering administrative dimension, socio-economic dimension, and environmental dimension, this study focuses on migrants with settlement intention and examines the impact of administrative level, city tier, and air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…While in the higher administrative level of the city, the negative impact of air pollution on the floating population's settlement intention is smaller, and the role of air quality also varies among different regions. Our findings are also consistent with those Wang et al [47], who found that city administrative level and air quality play an important role in shaping the willingness of hukou conversion for migrants with settlement intention. The findings of this paper provide new empirical evidence for research on the settlement intention of floating population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While in the higher administrative level of the city, the negative impact of air pollution on the floating population's settlement intention is smaller, and the role of air quality also varies among different regions. Our findings are also consistent with those Wang et al [47], who found that city administrative level and air quality play an important role in shaping the willingness of hukou conversion for migrants with settlement intention. The findings of this paper provide new empirical evidence for research on the settlement intention of floating population.…”
Section: Discussionsupporting
confidence: 93%
“…They found that the willingness to settle by the floating population in southern Jiangsu with a higher level of socioeconomic development was higher than that in northern Jiangsu with a lower level of socioeconomic development [46]. The spatial location of cities also has a significant impact on the settlement intention of the floating population, and show obvious regional differences [47].…”
Section: City Characteristics and Migrants' Settlement Intentionsmentioning
confidence: 99%
“…These 638 CRNs were working at 58 cities across China, most commonly in first-tier cities (49.37%) or emerging first-tier cities (30.41%) by definition of city tiers in China (Wang et al, 2021) (Table 2). In other words, these CRNs were mostly working in the largest Chinese cities with the highest socio-economic development level and future potential.…”
Section: Demographics Background Information and Professional Experiencementioning
confidence: 99%
“…Yicai Global, a Chinese news source, categorizes Chinese cities into six tiers using the five measures below: concentration of commercial resources; city’s pivotability; citizen vitality; lifestyle diversity; and flexibility in the future. The Yicai classification resulted in: 4 Tier 1 cities, 15 emerging Tier 1 cities, 30 Tier 2 cities, 70 Tier three cities, 90 Tier 4 cities and 129 Tier 5 cites (China Briefing, 2017; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Population migration has always been an important focus for academia (Abel & Sander, 2014;Hughes, 2019;Mulder et al, 2020;C. Wang et al, 2021;S.…”
Section: Theorymentioning
confidence: 99%